Overlooked role of heterotrophic prokaryotes in sulfur oxidation makes the sediment of the Bohai Sea a sufficient sink of hydrogen sulfide - Zhiyi Chen; Luying Xun; Yongzhen Xia; Xianzhe Gong (mBio)
ABSTRACT Marine sediments are the active sites for the biogeochemical cycling of sulfur. Sulfate is used as a major terminal electron acceptor for the anaerobic oxidation of organic compounds in deep sediments, and the produced sulfide is normally oxidized back to sulfate in upper sediments. However, it is unclear which microorganisms, metabolic pathways, and enzymes are mainly involved in oxidation. Here, we used metagenomics, metatranscriptomics, and the testing of sulfide, thiosulfate, and sulfite oxidation in sediment samples to figure out how sulfide is oxidized in the Bohai Sea sediments. Surprisingly, sulfur oxidation is widespread in the microbial community (>67.1%) of mostly heterotrophic prokaryotes across 44 phyla, dominated by Proteobacteria. Known chemolithotrophic sulfur oxidizers were absent. The prevalent sulfur-oxidizing pathway was sulfide to zerovalent sulfur, sulfite, and then sulfate. Thiosulfate is not a major metabolic intermediate. Genes encoding sulfide oxidation (sqr and fccAB), zerovalent sulfur oxidation (pdo, rdsrAB, and shdr), and sulfite oxidation (aprAB/sat) were abundant and upregulated after adding NaHS. Thiosulfate, which is formed between the reaction of zerovalent sulfur and sulfite, was only slowly oxidized, which was consistent with the lack of key genes encoding for direct oxidation of thiosulfate to sulfate. The findings indicate how sulfur is oxidized in the Bohai Sea sediments. The common participation in sulfur oxidation by most heterotrophic prokaryotes results in the effective oxidation of sulfide in the surface sediment, blocking the release of hydrogen sulfide into the water column.IMPORTANCESulfur cycling is tightly interwoven with other crucial element cycles, including carbon, nitrogen, and iron in marine sediments. Sulfate is the most abundant electron acceptor in marine sediments, and sulfate reduction generates a large amount of sulfide. The majority of sulfide is oxidized to sulfate via abiotic or biological transformations, mainly by sulfur oxidizers with different redox states. However, autotrophic sulfur oxidizers, considered key players for sulfur oxidation, are in low abundance in the sediment, limiting our understanding of the pivotal biogeochemical process. This study shows the prevalent distribution of sulfur oxidation among the microbial community and emphasizes the importance of heterotrophic sulfur oxidation in sediments. It evidences the importance of previously overlooked key enzymes for elemental sulfur oxidation and supports that thiosulfate is not the major intermediate during sulfur oxidation. Understanding these key processes is crucial for elucidating biogeochemical processes in marine sediments.